2005
DOI: 10.1038/sj.ejcn.1602333
|View full text |Cite
|
Sign up to set email alerts
|

LDL particle size, fat distribution and insulin resistance in obese children

Abstract: Background: The importance of small dense low-density lipoprotein (sdLDL) cholesterol in coronary heart disease has been demonstrated in many studies. Body fat accumulation, especially abdominal adiposity, is one of the important factors modifying the expression of sdLDL in adults. Objective: To determine the prevalence of sdLDL in obese children, and to investigate its relationship with anthropometric and metabolic variables. Subjects: A total of 30 obese children (22 males, 8 females) aged 12.670.6 years (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
2
14
2
2
Order By: Relevance
“…The association between total and LDL cholesterol and LDL particle size is not very consistent in children. In some studies, total and LDL cholesterol concentrations were similar between pattern B and pattern A subjects [1,18,25], whereas both total and LDL cholesterol were found to be lower in pattern B children in the study by Shimabukuro and co-workers [33]. Interestingly, our study showed that increasing total and LDL cholesterol concentration results in an increase in mean LDL particle size.…”
Section: Discussioncontrasting
confidence: 50%
“…The association between total and LDL cholesterol and LDL particle size is not very consistent in children. In some studies, total and LDL cholesterol concentrations were similar between pattern B and pattern A subjects [1,18,25], whereas both total and LDL cholesterol were found to be lower in pattern B children in the study by Shimabukuro and co-workers [33]. Interestingly, our study showed that increasing total and LDL cholesterol concentration results in an increase in mean LDL particle size.…”
Section: Discussioncontrasting
confidence: 50%
“…Both small, dense LDL and HDL particles in the current study of obese children were higher when compared to the data from healthy children in the study by Zeljkovic et al (22). A prevalence of small, dense LDL particles in obese children has been previously reported, although the results were not entirely consistent (9). In contrast, a relationship of small HDL particles with childhood obesity has been firmly established (23).…”
Section: Discussioncontrasting
confidence: 69%
“…Although increased lowdensity lipoprotein (LDL)-cholesterol (LDL-C) and low high-density lipoprotein (HDL)-cholesterol (HDL-C) concentrations are well-known as major atherosclerosis risk factors, it is now recognized that certain lipoprotein subclasses, particularly small, dense LDL and HDL, may further distinguish an individual's CVD risk (8). In accordance, atherogenic dyslipidemia has emerged as an increasingly prevalent risk factor in children, concomitant with obesity (9).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to secondary dyslipidemia, 54% of obese adolescents included in a study were characterized by phenotype B [14]; according to existing literature only 2-13% of the healthy pediatric population is characterized by this phenotype [15-22]. In a later study, forty percent of obese children with lipid abnormalities were found to have sdLDL particles [23]. This predominance is even more profound in children and adolescents with diabetes mellitus, reaching 86.7%, whereas only 11% of controls belonged to phenotype B. Additionally, youths with diabetes had significantly smaller mean LDL diameter than controls [24].…”
Section: Discussionmentioning
confidence: 99%